Mapping the Clinical Care Pathway of Fragility Fracture Patients at a German Maximum Care Provider Through Qualitative Research - Köhalmi, Gábor; Dirks, Patrick; Fass, Dorian; Bley, Romy; Pannen, Hans Derk; Kuhlen, Ralf; Bollmann, Andreas; Voigt, Nina; Kraft, Clayton (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
Osteoporosis is a chronic underdiagnosed condition that weakens bone structure with increased risk of fragility fractures. While the prevalence of osteoporosis is expected to increase due to demographic developments in many countries, there is found to be a serious treatment gap for patients. This is partly due to inadequate diagnostic procedures at healthcare facilities. Considering this, there is a need to understand factors that affect processes involving diagnosis and treatment in osteoporotic patients. This study’s primary aim is to explore the management of patients with fragility fractures and osteoporosis by conducting and analyzing semi-structured interviews with healthcare professionals at a German maximum care provider. Insights from the interviews were used to map out the pathway of clinical care for patients and the results suggest a multitude of factors including disease awareness, communication, and up-to-date information to be particularly important for increased treatment quality. Future studies shall focus on improving generalizability and exploring the effectiveness of recently updated guidelines for management of osteoporosis.
Keywords: osteoporosis; fragility fractures; clinical care pathway; qualitative research; pathway